Śmieci modne, czyli wykorzystanie produktów ekologicznych i recyclingowych w modzie i designie - Frączkiewicz, Marta (Studia Etnologiczne i Antropologiczne, 2017)
Caring for the environment is no longer limited only to waste segregation. Ecology has become a fashion statement, wich concerns many areas of life. Fashion and utility designers, as well as consumers use more and more materials, which have been considered garbage, not only giving them the proverbial “second life”, but also multiplying their original value. The purpose of this article is to describe the range of possibilities, which use recycled products in fashion and design gives, to the reader. I will also try to explain the most important terms as upcycling or downcycling. I will present the position of a number of Polish researchers towards contemporary eco-fashion.